2021
DOI: 10.1038/s41598-021-96730-9
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of progenitor cells and vessel healing after implantation of SYNERGY in acute coronary syndrome

Abstract: This study was aimed to compare the vascular healing process of a SYNERGY stent with that of a PROMUS PREMIER stent in patients with acute coronary syndrome (ACS). In 71 patients with ACS, undergoing coronary stent implantation using the SYNERGY stent (n = 52) or PROMUS PREMIER stent (n = 19), we measured circulating CD34+/CD133+/CD45null cells and CD34+/KDR+ cells and observed vascular healing at the stented sites using optical coherence tomography (OCT) and coronary angioscopy. On the day 7, circulating CD34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Notably, the same authors also reported differences in the counts of CD34+/CD133+/CD45 null and CD34+/KDR+ cells based on the stent type (with a larger response for a newer-generation ultra-thin strut DES as compared to a second-generation DES) group. Neointimal thickness and neointimal coverage rate were proportionally greater in the former [69]. In the paper by Pelliccia, 30 of the 155 patients showed in-stent restenosis at 8 months.…”
Section: Progenitor Cells Counts and Outcome After Stentingmentioning
confidence: 90%
“…Notably, the same authors also reported differences in the counts of CD34+/CD133+/CD45 null and CD34+/KDR+ cells based on the stent type (with a larger response for a newer-generation ultra-thin strut DES as compared to a second-generation DES) group. Neointimal thickness and neointimal coverage rate were proportionally greater in the former [69]. In the paper by Pelliccia, 30 of the 155 patients showed in-stent restenosis at 8 months.…”
Section: Progenitor Cells Counts and Outcome After Stentingmentioning
confidence: 90%